3D Printed Adapter to Commercial Electronic Micropipettes for Electroanalysis Directly Inside Disposable Tips. Issue 10 (5th August 2018) - Azevedo, Gustavo Chevitarese; Quirino, Welber Gianini; Matos, Maria Auxiliadora Costa; Matos, Renato Camargo
Abstract: The aim of this paper was to design a low cost 3D printed adapter to commercial micropipette that allows a pipette tip to be used as an electrochemical cell, for measurements at a microelectrode. This device combine the advantages of microelectrodes, electronic micropipettes and disposable tips for direct electrochemical analysis. The 3D printed device was used as a proof of concept, to analyze the voltammetric behavior of ferrocene using gold microelectrode in N, N‐Dimethylformamide (DMF) by square wave voltammetry (SWV), showing good response in non‐aqueous medium. The developed adapter was also tested for modifying a gold electrode directly inside a pipette tip, using only 10 μL of modification solution, with further dopamine analysis. The developed methodology was applied for determining dopamine in tap water samples as a proof of principle. The system was evaluated for repeatability (RSD 4 %, n=50), and reproducibility (RSD 4 %), indicating good performance for the considered concentration level. The work developed shows the efficacy and reliability of the constructed device, applicable to electrochemical analysis both in aqueous or non‐aqueous media. Abstract :